2006
DOI: 10.1111/j.1464-5491.2005.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Sick day management using blood 3‐hydroxybutyrate (3‐OHB) compared with urine ketone monitoring reduces hospital visits in young people with T1DM: a randomized clinical trial

Abstract: Blood ketone monitoring during sick days appears acceptable to and preferred by young people with Type 1 diabetes. Routine implementation of blood 3-OHB monitoring for the management of sick days and impending DKA can potentially reduce hospitalization/emergency assessment compared with urine ketone testing and offers potential cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 34 publications
2
129
0
5
Order By: Relevance
“…The most common cause of DKA in insulin pump users is failure to take extra insulin with a pen or syringe when hyperglycemia and hyperketonemia or ketonuria occur. Home measurement of blood ␤-OHB, when compared with urine ketone testing, decreases diabetes-related hospital visits (both emergency department visits and hospitalizations) by the early identification and treatment of ketosis (111). Blood ␤-OHB measurements may be especially valuable to prevent DKA in patients who use a pump because interrupted insulin delivery rapidly leads to ketosis.…”
Section: Prevention Of Dkamentioning
confidence: 99%
“…The most common cause of DKA in insulin pump users is failure to take extra insulin with a pen or syringe when hyperglycemia and hyperketonemia or ketonuria occur. Home measurement of blood ␤-OHB, when compared with urine ketone testing, decreases diabetes-related hospital visits (both emergency department visits and hospitalizations) by the early identification and treatment of ketosis (111). Blood ␤-OHB measurements may be especially valuable to prevent DKA in patients who use a pump because interrupted insulin delivery rapidly leads to ketosis.…”
Section: Prevention Of Dkamentioning
confidence: 99%
“…Previous work has shown that urine ketone strips can be used as a means of admission avoidance in an adult population when combined with advice by telephone [67]. Other authors have looked at the use of capillary ketone meters in a pediatric population and found that overall emergency room visits and admissions were significantly reduced (not just for DKA) [68]. These data suggest that the use of ketone meters in the prevention of DKA and subsequent hospitalization make the technology cost-effective.…”
Section: Costmentioning
confidence: 96%
“…Estudos mais recentes têm sugerido que a dosagem capilar de BHB possa também ser extremamente útil para o diagnóstico domiciliar de CAD incipiente, facilitando a recuperação precoce. É recomendada a medida domiciliar de cetonemia no sangue capilar ou cetonúria com fita reagente própria para pacientes com DM1 com hiperglicemia persistente acentuada (≥ 300 mg/dL ou até menos, a critério clíni-co), especialmente na vigência de stress ou quadros infecciosos (40)(41)(42)(43)(44).…”
Section: Cetonemiaunclassified